William Montgomery Brown (1855 - 1937): the Southern Episcopal bishop who became a communist - Carden, Ronald M. (Mellen, 2007)
The early years, 1855-1883 -- Clerical career in Ohio, 1878-1897 -- Arkansas : election and confirmation as Bishop Coadjutor, 1879-1898 -- Bishop of Arkansas, 1899-1911 -- The level plan of church union and materialism, 1910-1916 -- Marxism and communism and Christianism, 1917-1920 -- Prelude to the trial, 1920-1924 -- The court for the trial of a bishop, 1924 -- Court of review, publicity, and deposal, 1924-1925 -- The last years, 1925-1937